Coping Stress in Thyroid Cancer Patients - Zalfa, Adelia; Wahyuni, Endang; Pribadi, Eko Teguh (International Conference on Sustainable Health Promotion, 2025)
A diagnosis of thyroid cancer often triggers stress that affects the physical and psychological condition of patients. This study aims to explore the stress coping strategies used by thyroid cancer patients in facing health challenges. This qualitative study uses a case study approach with purposive sampling, involving subjects relevant to the research objectives. The results show that subjects apply problem-focused coping strategies, such as seeking medical information and planning treatment, as well as emotion-focused coping, such as utilizing social support and maintaining emotional stability. The implications of this study indicate that good stress coping is very important to reduce the negative psychological and physical effects caused by cancer. Conversely, poor coping can worsen the quality of life of patients and increase other risks. This study emphasizes the importance of insight in managing stress more effectively